DEVELOPING A CTL-BASED MANIPULATIVE WORKSHEET FOR FRACTION LEARNING IN GRADE 4 - Nuba Sanzania; Unik Ambar Wati (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2026)
Mathematics learning in elementary schools requires instructional materials that can connect abstract concepts with students’ real-life experiences. One of the common difficulties faced by students in learning fractions is understanding the part–whole relationship, which is often caused by limited use of manipulative media and teacher-centered instructional practices. This study aims to develop a Contextual Teaching and Learning (CTL)-based manipulative worksheet and to examine its effectiveness in improving elementary school students’ fraction learning outcomes. This study employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were 23 fourth-grade elementary school students. Data were collected through observations, documentation, and learning outcome tests in the form of pretest and posttest, which were administered at the evaluation stage to measure students’ learning improvement after the implementation of the worksheet. The results of the study indicate that the CTL-based manipulative worksheet was effective in improving students’ fraction learning outcomes. The average pretest score was 61.85, which increased to 81.70 in the posttest. The difference between pretest and posttest scores was 19.85 points, representing an improvement of 32.09%. In addition to improved learning outcomes, students demonstrated higher engagement during the learning process through manipulative activities and contextual discussions. In conclusion, the developed CTL-based manipulative worksheet is feasible and effective as an instructional material to support meaningful fraction learning in elementary schools.